(untitled) (Journal of Economic Research & Business Administration, 2021)
The aim of the study is to assess various factors affecting consumers when purchasing goods and services during COVID-19. In today’s constantly changing and highly unpredictable corporate environment, companies and enterprises need to develop a high degree of understanding of the dynamics of purchasing behavior and the skills of their customers in order to predict various changes. The study also attempted to get consumer opinion on online marketing. a quantitative research methodology was applied to collect the opinions of 300 consumers from Almaty and Kostanay regions using a three-part questionnaire using a reliability test to validate the questionnaire. Based on the current pandemic situation, the authors of this paper initiated a study to examine the dynamics that influenced consumer buying behavior in the second quarter of 2020. The selected hypotheses were tested using the Pearson chisquare test. It is shown that purchasing power is largely influenced by the factors of prices for goods and services, while other factors such as promotion, salespeople, processes, physical environment have a nominal influence on the purchasing behavior of consumers. COVID-19 is the main reason for choosing online marketing to buy products and services. The results of this study can be useful for both domestic and foreign marketers working in our republic in order to successfully promote products and services among consumers. Key words: purchasing power, consumers, couder-richardson test (kr-20), internet marketing, factors, prices.